Comparison of Kaltenborn mobilization technique and muscle energy technique on range of motion, pain and function in subjects with chronic shoulder adhesive capsulitis - Pattnaik, Sandeep; Kumar, Pravin; Sarkar, Bibhuti; Oraon, Anil Kumar (Hong Kong physiotherapy journal, 2023)
Background: Shoulder adhesive capsulitis (AC) is a common musculoskeletal condition causing pain, loss of range of motion (ROM) in the shoulder, and a decrease in its functionality, yet poorly defined and understood since its identification. Kaltenborn mobilization technique (KMT) and muscle energy technique (MET) are commonly used physiotherapeutic techniques for their treatment. To the best of our understanding, there was no study found to compare the effectiveness of one technique over another. Objective: The objective of this study was to compare the effectiveness of KMT and MET on the ROM, pain and function in subjects with chronic shoulder AC. Methods: In this single-centred, single-blinded quasi-experimental study with a pretest–posttest design 35 subjects were randomized into two groups: Group A ( n = 1 8 ) received KMT and Group B ( n = 1 7 ) received MET along with the moist hot pack (MHP), supervised exercises and home exercises common to both the groups. A total of 32 subjects completed the study with three dropouts. Subjects were evaluated before and after 10 treatment sessions for the outcomes, shoulder external rotation passive range of motion (ER-PROM) and abduction passive range of motion (ABD-PROM) using the universal goniometer, intensity of pain using the numeric pain rating scale (NPRS) and functional disability using the shoulder pain and disability index (SPADI). Results: Analysis of 32 subjects showed that both groups were homogenous at baseline. The within-group analysis showed significant improvement ( p < 0 . 0 5 ) in both groups related to all the outcomes. But when we compared the groups, Group B showed significant ( p < 0 . 0 5 ) improvement in NPRS and SPADI in comparison to Group A. However, there was non-significant ( p > 0 . 0 5 ) difference found in ER-PROM and ABD-PROM. Conclusion: Both KMT and MET are effective in improving ROM, pain and function but MET showed a significant reduction of pain and improvement in function in subjects with chronic shoulder AC, thus supporting its use as a physiotherapeutic treatment technique.